Business Development Services of Cooperatives and Financial Performance of Dairies: A Case from Kavrepalanchok District, Nepal (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study explores the influence of Business Development Services (BDS) on the financial performance of dairies in Kavrepalanchok district, Nepal, which are vital for improving rural farmers’ livelihoods by providing input supply, infrastructure, and technical training.Methods: The study analyzed data from 244 dairy cooperative members in Mandan Deupur Municipality, Kavrepalanchok district using a survey and a five-point Likert scale. Reliability and normality were tested using Cronbach’s Alpha, one-sample t-test, Kolmogorov-Smirnova test, and Shapiro-Wilk test. Regression analysis was conducted to examine the impact of business development services on dairy financial performance.Results:The study found that market accessibility and training for farmers in dairy products enhance productivity, quality, and sales turnover. However, farmers did not receive better training and technical assistance than expected. Input supply services from dairy cooperatives were not a concern for farmers. Infrastructure support, particularly in milk transportation and storage, is crucial for maintaining product quality and market access, impacting revenue generation.Conclusion: BDS enhances financial stability, but challenges persist in marketing skills and technical knowledge, necessitating improvements for enhanced cooperative performance.